Use of biological markers for detection of the atypical flora in children with recurrent bronchopulmonary diseases - Bessikalo, T.; Plokhushko, V.; Бессікало, Тетяна Григорівна; Плохушко, Віталій Вікторович (publishing center of the ESCBM, The Czech Republic, 2018)
Pathology of the respiratory system is the leading in the structure of childhood diseases. Recurrent bronchopulmonary pathology in children remains difficult for differentiating and requires use of combination of methods. The similarity and recurrence of symptoms of bronchitis caused by different health problems underlines importance of biological markers. The aim of the research was to assess roel of biological markers for evaluation of the role of the atypical flora in the course of recurrent bronchopulmonary diseases in children.
Keywords: тези доповідей; children; IgM; recurrent bronchitis; bronchial asthma